The Application of BMS in Electrical Energy Management and Carbon Emission Reduction - Thi Mong Nhi Bui,; Tung Giang Tran,; Hoang Trung Nguyen,; Minh Tri Bui,; Tieu Long Nguyen,; Hoang Minh Nguyen,; Thi Ngoc Thuan Le,; Dang Linh Bui,; Thi Thu Lanh Le,; Minh Tuan Tram, (Journal of Technical Education Science, 2024)
This article presents the application of Building Management System (BMS) in electrical load management. The BMS system in this article structure includes DDC, IOT 2050 Siemens, sensors, inverters and loads. Implementing this system in buildings saves energy, reduces operating costs and reduces CO2 emissions. A comparative analysis was conducted between projects with and without BMS implementation. The investment in the BMS incurs an additional capital expenditure, with a payback period of 7.3 years and a system lifespan of 20 years, providing a return of more than 13% on the investment. The results show significant energy savings with total consumption reduced by 13%. These findings highlight the effectiveness of BMS in optimizing energy use across different areas of a building, providing significant financial and environmental benefits. This research contributes to understanding the economic and environmental implications of integrating BMS into infrastructure development, creating favorable conditions for stakeholders in the construction and energy sectors.